A Collaborative Approach in Women Empowerment: Experience from Garut Regency - Nefi Aris Ambar Asmara; Rike Anggun Artisa (Jurnal Ad'ministrare, 2021)
This paper discusses the collaborative governance process in empowering women in Garut Regency through the Integrated Program for Increasing the Role of Women Towards Healthy and Prosperous Families. This program is an annual routine program to increase the role of women in development in the village scope. This program involves various stakeholders, from elements of government, non-government organizations, the private sector, universities, and other elements of society. This study uses a qualitative method with a descriptive approach. Data was collected by interviewing relevant informants and observing the target villages. The results show that this collaborative governance process has a strong impetus to increase women's participation. The main supporting factors for collaboration are leadership and shared goals from stakeholders. The next empowerment challenge is how to make women able to maintain their participation after the program ends.